2016
DOI: 10.1021/acs.biochem.6b00063
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin Gallate Remodels Fibrils of Lattice Corneal Dystrophy Protein, Facilitating Proteolytic Degradation and Preventing Formation of Membrane-Permeabilizing Species

Abstract: Lattice corneal dystrophy is associated with painful recurrent corneal erosions and amyloid corneal opacities induced by transforming growth factor β-induced protein (TGFBIp) that impairs vision. The exact mechanism of amyloid fibril formation in corneal dystrophy is unknown but has been associated with destabilizing mutations in the fourth fasciclin 1 (Fas1-4) domain of TGFBIp. The green tea compound epigallocatechin gallate (EGCG) has been found to inhibit fibril formation of various amyloidogenic proteins i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 71 publications
1
5
0
Order By: Relevance
“…EGCG, despite being infamous as a promiscuous ligand, fulfills these requirements: It precipitates preferentially the amyloidogenic V L domains. A similar selectivity of EGCG for amyloidogenic mutants was recently reported for TGFBIp 64 . At the same time, the EGCG binding site in functional antibodies is hidden, as the binding site is protected by the heavy chain.…”
Section: Discussionsupporting
confidence: 85%
“…EGCG, despite being infamous as a promiscuous ligand, fulfills these requirements: It precipitates preferentially the amyloidogenic V L domains. A similar selectivity of EGCG for amyloidogenic mutants was recently reported for TGFBIp 64 . At the same time, the EGCG binding site in functional antibodies is hidden, as the binding site is protected by the heavy chain.…”
Section: Discussionsupporting
confidence: 85%
“…In the above experiments, we set out to investigate whether EGCG exerts a potentially protective effect on apoA-I amyloid that is associated with atherosclerosis, as reported for several other amyloidogenic proteins associated with disease ( 49 , 50 ). Studies on Aβ40/42, α-synuclein, amylin, huntingtin, and transthyretin have all shown a common ability of EGCG to bind to the oligomeric and multimeric forms of amyloid, to inhibit fibril assembly, and to prevent formation of toxic structures ( 28 , 29 , 51 55 ). In the case of both Aβ40/42 and α-synuclein, EGCG prevents fibrillogenesis by binding preferentially to unfolded protein, directing assembly toward off-pathway nontoxic oligomers, and thereby preventing formation of toxic oligomers and protofibrils ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Often these mutations result in amino acid substitutions that alter protein charge, hydrophobicity or tendency to form β-sheet secondary structures . Indeed, in TGFBI -linked corneal dystrophy, the disease-associated mutations encode proteins that are either thermodynamically unstable (A546T) or overly stable (R555W [PDB 2LTC] and G623D) relative to the native protein. Where unstable mutant proteins are produced, excessive proteolysis may generate highly amyloidogenic peptide fragments. Conversely, enhanced protein stability may increase the turn over time of the protein in the cornea and possibly prevent effective protein clearance which is highly essential to maintain transparency of the cornea .…”
Section: Discussionmentioning
confidence: 99%